Instructors’ Perceptions of Instructor Presence in Online Learning Environments - Richardson, Jennifer C.; Besser, Erin; Koehler, Adrie; Lim, JiEun; Strait, Marquetta (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
As online learning continues to grow significantly, various efforts have been explored and implemented in order to improve the instructional experiences of students. Specifically, research indicates that how an instructor establishes his or her presence in an online environment can have important implications for the students’ overall learning experience. While instructor presence appears to be an important aspect of online learning, more research is needed to fully understand this construct. The purpose of this study was to consider online instructors’ perceptions related to presence, beliefs about actions, and the perceived impact of instructional presence. Using an explanatory multiple-case study approach, this research considered the perspectives of 13 instructors teaching in an online master’s program at a large Midwestern public university. Results indicate instructors viewed instructor presence as an important component in online courses but their reasons varied. Furthermore, the instructors discussed a number of communication strategies they used, the importance of using such strategies to connect to students, and the potential impact of these strategies on student participation and learning. Additional themes from the interview data are discussed, and implications for online teaching and learning are suggested.